ANCA‐associated neuropathy in systemic sclerosis: A case report and review of literature - Kayo Takenaka; Takuya Takeichi; Ryoji Nishi; Masashi Suzuki; Haruki Koike; Masahisa Katsuno; Mariko Ogawa‐Momohara; Yoshinao Muro; Masashi Akiyama (Frontiers Media S.A., 2021)
Abstract Systemic sclerosis (SSc) is a multi‐system autoimmune disease. Anti‐neutrophil cytoplasmic antibodies (ANCA) are autoantibodies directed against enzymes found within primary granules of neutrophils and lysosomes in monocytes. Although up to 12% of SSc patients have ANCA, only a minority of these patients develop an overlap syndrome with ANCA‐associated vasculitis. We summarize previous reports on SSc patients with ANCA‐associated neuropathy. In all the reported cases, the SSc diagnosis preceded the ANCA‐associated neuropathy diagnosis. Seven of the eight patients with limited cutaneous SSc had interstitial lung disease (ILD). Thus, patients with ANCA‐associated neuropathy in lSSc may be prone to complication with ILD.